CRISPR/Cas systems: Delivery and application in gene therapy - Huang, Jie; Zhou, Yitong; Li, Jie; Lu, Aiping; Liang, Chao (Frontiers in Bioengineering and Biotechnology, 2022)
The CRISPR/Cas systems in prokaryotes such as bacteria and archaea are the adaptive immune system to prevent infection from viruses, phages, or other foreign substances. When viruses or phages first invade the bacteria, Cas proteins recognize and cut the DNA from viruses or phages into short fragments that will be integrated into the CRISPR array. Once bacteria are invaded again, the modified CRISPR and Cas proteins react quickly to cut DNA at the specified target location, protecting the host. Due to its high efficiency, versatility, and simplicity, the CRISPR/Cas system has become one of the most popular gene editing technologies. In this review, we briefly introduce the CRISPR/Cas systems, focus on several delivery methods including physical delivery, viral vector delivery, and non-viral vector delivery, and the applications of disease therapy. Finally, some problems in CRISPR/Cas9 technology have been proposed, such as the off-target effects, the efficiency of DNA repair mechanisms, and the delivery of the CRISPR/Cas system safely and efficiently to the target location.